Śāntideva and Paul—An Unexpected Encounter - Schmidt-Leukel, Perry (Buddhist Christian studies, 2021)
This essay is based on my commentary on the Bodhicaryāvāra in which I discovered and explored a striking similarity between the Pauline tension of spirit and flesh on the one hand and Śāntideva's description of the tension between spirit and defilements on the other hand. By means of a fictive dialogue between Paul and Śāntideva, the essay provides a brief summary of the broader theological and buddhological contexts in which these two conceptions of spiritual endeavor are embedded. In doing so, further parallels but also differences between the teachings of Paul and Śāntideva are highlighted, suggesting that the commonalities are strong enough to indicate a common spiritual source and the differences significant enough to enable reciprocal illumination in terms of a genuinely truth-seeking dialogue.